The impact of parental supervision and school environmental factors on cyberbullying behavior among students - Khodijah, Siti; Firmasyah , Ridwan; Komalasari , Winda; Tusyahri , Alfiah; Sandria , Gatari; Pathurrahman , Pajri (At-Tajdid: Jurnal Ilmu Tarbiyah, 2024)
This study investigates the influence of parental supervision and school environment factors on cyberbullying behaviors among elementary school students. A regression analysis method was employed, with a sample drawn from MI Tabiyatul Athfal in East Jakarta. The findings reveal that both parental supervision and the school environment significantly affect cyberbullying behaviors. Enhanced parental monitoring and a supportive school environment can reduce cyberbullying incidents. This research provides new insights into factors influencing cyberbullying, crucial for effective prevention and intervention strategies in schools and homes.